2011
DOI: 10.1149/1.3592484
|View full text |Cite
|
Sign up to set email alerts
|

Cold Start of a Polymer-Electrolyte Fuel Cell II. Model Verification Using Parametric Studies

Abstract: The cold-start model developed in Part I of this study is verified by comparing its predictions to a variety of experiments in the literature. Using the model, the physical bases for trends observed in various parametric studies are explained. For example, it is shown that near but below 0 C, liquid water flow out of the cathode catalyst layer enables the cell to operate for a significantly longer time than it could if no liquid flow occurred. It is also shown that increasing the current density during start-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…• C. 9 The work by Thompson et al has demonstrated that PEM thickness and the anode CL do not significantly contribute to differences in the water storage capacity. 32 To confirm the absence of PEM type/thickness, an additional baseline Sprayed CL was applied to Nafion NR-212 to directly compare to Decal CLs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C. 9 The work by Thompson et al has demonstrated that PEM thickness and the anode CL do not significantly contribute to differences in the water storage capacity. 32 To confirm the absence of PEM type/thickness, an additional baseline Sprayed CL was applied to Nafion NR-212 to directly compare to Decal CLs.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Initially an OCV was established greater than 0.97 V and then a small constant load of 10 mA cm −2 was applied. The cell voltage and cell resistance (via current interrupt) were monitored.…”
Section: Water Fill Tests-the Isothermal Wfts Were Performed At Subzmentioning
confidence: 99%
“…According to the literature, the dominant subzero PEMFC studies investigating the influence of material and operational parameters have been restricted to subscale single-cell freeze-thaw testing [3][4][5][6][7][8][9][10][11][12][13][14], isothermal water fill tests , and non-isothermal water fill tests [3,21,33,[38][39][40][41][42][43][44][45][46][47]. United Technology Corporation (UTC) Power and its corporate research facility co-developed two quasi-adiabatic single PEMFC fixtures in the mid-2000s with geometric active areas of 25 cm 2 and 320 cm 2 [48][49][50]. The results demonstrated that it was possible under a galvanic load cold-start to replicate the center cells in a stack's voltage and thermal profile in the quasi-adiabatic fixture.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that it was possible under a galvanic load cold-start to replicate the center cells in a stack's voltage and thermal profile in the quasi-adiabatic fixture. Balliet and Newman validated their two-dimensional liquid water transport cold-start model to the UTC-Power's quasi-adiabatic PEMFC fixture performance profiles [49]. However, the inadequate structural integrity of the quasi-adiabatic PEMFC fixture limited its reusability.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal studies have focused on understanding mechanisms of water storage in the membrane/cathode catalyst layer (8). Recent non-isothermal modeling and experiments of cold start suggest that adverse negative voltages occur at cold starts below -20°C due to low ionomer ionic conductivity (9).…”
Section: Introductionmentioning
confidence: 99%